Complete Genome Sequence of Bacteriophage phiAS7, a T7-Like Virus That Infects Aeromonas salmonicida subsp. salmonicida - Kim, Ji Hyung (American Society for Microbiology, 2012)
To date, a number of Myoviridae bacteriophages that infect Aeromonadaceae have been identified and characterized. However, the genome sequences of Aeromonas phages that not belong to the Myoviridae have not been investigated yet. Herein, we report the complete genome sequence of Aeromonas phage phiAS7, which belongs to the Podoviridae and infects Aeromonas salmonicida subsp. salmonicida.